The Armed Conflict in the Sahel Region and Efforts of the ECOWAS to Settle it - ZHAMBIKOV Alexander Мunirovich (Ученые записки Института Африки Российской академии наук)
The article describes the armed conflict in the Sahel region, lasting for ten years and affecting three countries: Burkina Faso, Mali and Niger. The objective of research is to characterise and assess the activities of the regional organisation ECOWAS in the context of Sahel peace-settlement. The Sahel conflict was a direct consequence of destruction of the Libyan state, as a result of the civil war and NATO military intervention in 2011, which created conditions for rebel invasion to Mali in January 2012.